Patterns of morphologic alteration correlate with vision in diabetic macular oedema: a cross‐sectional evaluation of patients using the SAVE II protocol. Issue 4 (17th November 2019) - Bolz, Matthias; Podkowinski, Dominika; Pretzl, Josef; Mursch‐Edlmayr, Anna‐Sophie; Luft, Nikolaus; Ring, Michael; ,
Abstract: Purpose: We sought to describe and evaluate patients with clinically significant diabetic macular oedema (CSME) according to the improved SAVE II protocol and correlate findings with visual acuity and systemic parameters in the outpatient clinic for DR (diabetic retinopathy) management. Methods: This was a cross‐sectional case series study of patients with CSME, regardless of prior treatment. Visual acuity testing was performed according to the Early Treatment of Diabetic Retinopathy Study (ETDRS) protocol. Optical coherence tomography (OCT) and fluorescence angiography (FA) were performed. All imaging data were evaluated according to an improved version of the SAVE grading protocol for CSME (SAVE II). The main outcome measures were SAVE II oedema types and best‐corrected visual acuity. Additional parameters of a blood sample (fasting glucose, haemoglobin A1c, serum creatinine, triglycerides, cholesterol, low‐density lipoproteins, and high‐density lipoproteins) were taken. Results: In total, 66 eyes of 66 patients were included. The mean age of the patients was 64.9 ± 8.2 years. Two eyes were classified as SAVE oedema type 1, 19 eyes as SAVE oedema type 2, 28 eyes as SAVE oedema type 3, and 28 eyes as SAVE oedema type 4, respectively. Central retinal thickness and laboratory parameters were not significantly different between the groups. There was a statistically significant difference in ETDRS visual acuity between the SAVE groups 2 and 4 (p < 0.001) with lower vision in group 4. There was no statistically significant difference between oedema types 2 and 3 (p = 0.065) and oedema types 3 and 4 (p = 0.13). Conclusion: There was a significant correlation between the four defined oedema types and visual acuity. Morphologic findings did not correlate with any of the evaluated blood parameters.